Sistema automatizado de riego basado en sensorización en los cultivos de ciclo corto en el sector la pastora - cantón Tosagua - Alcívar Domínguez, Christian Eduardo (2018)
The need of increasing the production in the agricultural sector by using the minimal of resources has become in a priority condition, but to make that possible, among others, it’s precise to manage the amount of water the crops need. This degree work presents the development of an automated irrigation system based on short-cycle crop sensoring in La Pastora – Tosagua sector, which has as a principal purpose to optimize water distribution. The Free Hardware Methodology was used for the development of the automatization prototype, it has three processes: design planification, production and device working tests, in addition to the evaluation of the land where it would be implemented, and the specialized technical advice received by experts in both irrigation systems and automation. The final device was installed in the selected land and controlled the irrigation of the crop from sowing to the harvest between June and September 2018, collecting data such as: soil moisture, humidity, temperature, among others. The visualization of the data was done through a developed desktop application using the Cascada methodology, this application facilitated the analysis of the data that show among its main results that the 37.27% decrease in water consumption was achieved, generating savings of $ 1.43 per sprinkler and an extra profit of $ 343 per hectare with respect to the traditional irrigation system, plus there was an improvement of 7.53% of productivity. The results presented show that intervention in the agro-productive sector is necessary with automated processes as a tool to improve productivity and reduce costs.